Fibonacci Sum

Calculus Level 5

n = 1 n F n 2 n = k n = 1 F n 2 n \sum_{n=1}^ \infty \dfrac{ n F_{n}}{ 2^n } = k{\sum_{n=1}^ \infty \dfrac{ F_{n}}{ 2^n }}

Let F n F_n denote the n th n^\text{th} Fibonacci number , where F 0 = 0 F_0 = 0 , F 1 = 1 F_1 = 1 and F n = F n 1 + F n 2 F_n = F_{n-1} + F_{n-2} for n = 2 , 3 , 4 , . . . . n=2,3,4, ....

Find the value of k k satisfying the equation above.


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let S ( x ) = n = 1 F n × x n S(x) = \sum_{n=1}^\infty F_n \times x^n , and T ( x ) = n = 1 n F n × x n T(x) = \sum_{n=1}^ \infty n\cdot F_{n} \times x^n . Then, we are interested in S ( 1 2 ) S( \frac{1}{2} ) and T ( 1 2 ) T ( \frac{1}{2} ) .

According to Fibonacci series , the sum of the power series can be written as:

n = 1 F n x n = x 1 x x 2 . \sum_{n=1}^\infty F_n x^n = \frac{x}{1-x-x^2}.

Setting x = 1 2 x =\dfrac{1}{2} , we obtain

n = 1 F n 2 n = 1 2 1 1 2 ( 1 2 ) 2 = 2. \sum_{n=1}^\infty \frac{F_n}{2^n} = \frac{\frac{1}{2}}{1-\frac{1}{2}-(\frac{1}{2})^2} = 2.

In order to evaluate T ( x ) T(x) , we will differentiate S ( x ) S(x) : n = 1 F n × n × x n 1 = S ( x ) = d d x ( x 1 x x 2 ) = 1 ( 1 x x 2 ) ( 2 x 1 ) ( x ) ( 1 x x 2 ) 2 = x 2 + 1 ( 1 x x 2 ) 2 . \sum_{n=1}^\infty F_n \times n \times x^{n-1} = S'(x)= \frac{d}{dx} \left( \frac{ x}{ 1- x- x^2 } \right) = \frac{1\cdot(1-x-x^2) - (-2x-1)(x)}{(1-x-x^2)^2} = \frac{x^2 +1}{(1-x-x^2)^2}.

Thus,

T ( x ) = n = 1 ( F n ) ( n ) x n = x S ( x ) = x 3 + x ( 1 x x 2 ) 2 . T(x) = \sum_{n=1}^\infty (F_n)(n) x^n = x\cdot S'(x) = \frac{x^3 +x}{(1-x-x^2)^2}.

Now, we can plug in x = 1 2 x =\dfrac{1}{2} to obtain:

T ( 1 2 ) = ( 1 2 ) 3 + 1 2 ( 1 1 2 ( 1 2 ) 2 ) 2 = 5 8 1 16 = 10 T(\frac{1}{2}) = \frac{(\frac{1}{2})^3 + \frac{1}{2}}{(1-\frac{1}{2}-(\frac{1}{2})^2)^2} = \frac{\frac{5}{8}}{\frac{1}{16}} =10

Therefore, T ( x ) = 5 S ( x ) T(x) = 5\cdot S(x) . As a result, k = 5 k = \boxed{5} .

As well there is the use of F n = ( 1 + 5 2 ) n ( 1 5 2 ) n 5 \displaystyle F_n = \frac{( \frac{1+\sqrt{5}}{2})^n - ( \frac{1-\sqrt{5}}{2})^n}{\sqrt{5}} directly for r value of n r n = r ( 1 r ) 2 \displaystyle\sum nr^n = \frac{r}{(1-r)^2}

First Last - 4 years, 6 months ago

Log in to reply

Oh, thank you for sharing.

Worranat Pakornrat - 4 years, 6 months ago

Good manipulation of the generating function !

Calvin Lin Staff - 4 years, 6 months ago

Log in to reply

Thank you. 😉

Worranat Pakornrat - 4 years, 6 months ago

FYI I've made several edits to make your solution read easier

  1. Redefined S ( x ) , T ( x ) S(x), T(x) . Previously they were F n x n \sum \frac{ F_n} { x^n} which would not work in the rest of the solution.
  2. Ensured that the equal signs were in the right order, so that people can follow from one to the next. E.g. instead of T ( x ) = x S ( x ) = n = 1 ( F n ) ( n ) x n T(x) = x\cdot S'(x) = \sum_{n=1}^\infty (F_n)(n) x^n , I made it T ( x ) = n = 1 ( F n ) ( n ) x n = x S ( x ) T(x) = \sum_{n=1}^\infty (F_n)(n) x^n = x\cdot S'(x)

Calvin Lin Staff - 4 years, 6 months ago

Log in to reply

Thank you. I'll try to improve next time.

Worranat Pakornrat - 4 years, 6 months ago
Ivan Koswara
Nov 22, 2016

Let a m = n = m F n 2 n \displaystyle a_m = \sum_{n=m}^\infty \frac{F_n}{2^n} . The LHS converges absolutely, and so can be rearranged into m = 1 n = m F n 2 n = m = 1 a m \displaystyle \sum_{m=1}^\infty \sum_{n=m}^\infty \frac{F_n}{2^n} = \sum_{m=1}^\infty a_m (to see this, note that F n 2 n \frac{F_n}{2^n} appears n n times, in m = 1 , 2 , , n m = 1, 2, \ldots, n ), and the RHS is simply k a 1 k a_1 . We will now compute a closed form expression for a m a_m .

On one hand, a m 1 = a m + F m 1 2 m 1 a_{m-1} = a_m + \frac{F_{m-1}}{2^{m-1}} or a m = a m 1 F m 1 2 m 1 a_m = a_{m-1} - \frac{F_{m-1}}{2^{m-1}} ; we simply take the term n = m 1 n = m-1 out of the summation. Applying this for m m 1 m \gets m-1 , we have a m 1 = a m 2 F m 2 2 m 2 a_{m-1} = a_{m-2} - \frac{F_{m-2}}{2^{m-2}} . Summing the two together, we also get a m = a m 2 F m 1 2 m 1 F m 2 2 m 2 a_m = a_{m-2} - \frac{F_{m-1}}{2^{m-1}} - \frac{F_{m-2}}{2^{m-2}} .

On the other hand, using the Fibonacci recurrence relation,

a m = n = m F n 2 n = n = m F n 1 + F n 2 2 n = n = m F n 1 2 n + n = m F n 2 2 n = n = m 1 F n 2 n + 1 + n = m 2 F n 2 n + 2 = 1 2 a m 1 + 1 4 a m 2 \displaystyle\begin{aligned} a_m &= \sum_{n=m}^\infty \frac{F_n}{2^n} \\ &= \sum_{n=m}^\infty \frac{F_{n-1} + F_{n-2}}{2^n} \\ &= \sum_{n=m}^\infty \frac{F_{n-1}}{2^n} + \sum_{n=m}^\infty \frac{F_{n-2}}{2^n} \\ &= \sum_{n=m-1}^\infty \frac{F_n}{2^{n+1}} + \sum_{n=m-2}^\infty \frac{F_n}{2^{n+2}} \\ &= \frac{1}{2} a_{m-1} + \frac{1}{4} a_{m-2} \end{aligned}

Using these relations, we can obtain the closed form:

a m = a m a m 2 F m 1 2 m 1 F m 2 2 m 2 = 1 2 a m 1 + 1 4 a m 2 a m 2 F m 1 2 m 1 F m 2 2 m 2 = 1 2 ( a m 2 F m 2 2 m 2 ) + 1 4 a m 2 1 4 a m 2 = F m 1 2 m 1 + 1 2 F m 2 2 m 2 a m 2 = F m 1 2 m 3 + F m 2 2 m 3 a m 2 = F m 2 m 3 \displaystyle\begin{aligned} a_m &= a_m \\ a_{m-2} - \frac{F_{m-1}}{2^{m-1}} - \frac{F_{m-2}}{2^{m-2}} &= \frac{1}{2} a_{m-1} + \frac{1}{4} a_{m-2} \\ a_{m-2} - \frac{F_{m-1}}{2^{m-1}} - \frac{F_{m-2}}{2^{m-2}} &= \frac{1}{2} \left( a_{m-2} - \frac{F_{m-2}}{2^{m-2}} \right) + \frac{1}{4} a_{m-2} \\ \frac{1}{4} a_{m-2} &= \frac{F_{m-1}}{2^{m-1}} + \frac{1}{2} \cdot \frac{F_{m-2}}{2^{m-2}} \\ a_{m-2} &= \frac{F_{m-1}}{2^{m-3}} + \frac{F_{m-2}}{2^{m-3}} \\ a_{m-2} &= \frac{F_m}{2^{m-3}} \end{aligned}

Thus, a m = F m + 2 2 m 1 a_m = \frac{F_{m+2}}{2^{m-1}} . Substituting this to the LHS gives

m = 1 a m = m = 1 F m + 2 2 m 1 = 8 m = 1 F m + 2 2 m + 2 = 8 m = 3 F m 2 m = 8 a 3 \displaystyle\begin{aligned} \sum_{m=1}^\infty a_m &= \sum_{m=1}^\infty \frac{F_{m+2}}{2^{m-1}} \\ &= 8 \sum_{m=1}^\infty \frac{F_{m+2}}{2^{m+2}} \\ &= 8 \sum_{m=3}^\infty \frac{F_m}{2^m} \\ &= 8 a_3 \end{aligned}

Now we can use our closed form expression to obtain a 1 = 2 , a 3 = 5 4 a_1 = 2, a_3 = \frac{5}{4} . Thus the LHS is equal to 8 a 3 = 10 8 a_3 = 10 , and the RHS is equal to k a 1 = 2 k k a_1 = 2k , so k = 10 2 = 5 k = \frac{10}{2} = \boxed{5} .

Note that this is easily generalizable for a different base of the denominator; most 2's are simply replaced by the appropriate base.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...